2011
DOI: 10.1002/ceat.201000422
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Trivalent Metal Ions on the Metastable Zone Width of Ammonium Sulfate

Abstract: The metastable zone width (MZW) is a vital parameter for the design of industrial crystallization processes of inorganic salts and could be affected by the addition of impurities. Here, the effect of the trivalent ions Fe 3+ , Cr 3+ , and Al 3+ on the MZW of ammonium sulfate was observed. All the experiments were performed with the help of ultrasonic speed measurements. Impurity concentrations up to 100 ppm at a solution pH of 4 increase the MZW depending on the metal ion. The pH value also showed a major infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…38 Trivalent ions Fe 3+ , Cr 3+ , and Al 3+ were reported to widen the MSZWs of ammonium sulphate, where the pH also played an important role in the effect of impurity ions. 34 The crystal size can be optimized with the content level of impurity in the solution. 31 In addition, study have shown that ultrasound can narrow the crystal size distribution and reduce agglomeration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Trivalent ions Fe 3+ , Cr 3+ , and Al 3+ were reported to widen the MSZWs of ammonium sulphate, where the pH also played an important role in the effect of impurity ions. 34 The crystal size can be optimized with the content level of impurity in the solution. 31 In addition, study have shown that ultrasound can narrow the crystal size distribution and reduce agglomeration.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] The nucleation process of ammonium sulphate crystallization has been reported. 4,5,[29][30][31][32][33][34][35] The influences of the existence of different impurity ions, 30,31,33,34,36 pH value, 5,32,35,37 and stirring speed 4,5 on the crystal habit and particle size distribution of ammonium sulphate have been investigated, which will also influence the morphology and size distribution of the final crystalline product. 38 Trivalent ions Fe 3+ , Cr 3+ , and Al 3+ were reported to widen the MSZWs of ammonium sulphate, where the pH also played an important role in the effect of impurity ions.…”
Section: Introductionmentioning
confidence: 99%